Facile synthesis of Ni11(HPO3)8(OH)6/rGO nanorods with enhanced electrochemical performance for aluminum-ion batteries. Issue 45 (13th November 2018) - Tu, Jiguo; Lei, Haiping; Wang, Mingyong; Yu, Zhijing; Jiao, Shuqiang
Abstract : A route to the large-scale synthesis of ultrashort nickel phosphite nanorods supported on reduced graphene oxide (Ni11 (HPO3 )8 (OH)6 /rGO nanorods) is presented. And the reversible reaction mechanism has been confirmed by utilizing the redox reaction of Al 3+ . Abstract : The electrochemical behaviors of the ultrashort nickel phosphite nanorods supported on reduced graphene oxide (Ni11 (HPO3 )8 (OH)6 /rGO nanorods), as a candidate for cathodic applications in aluminum-ion batteries, are firstly investigated. Ni11 (HPO3 )8 (OH)6 /rGO nanorods are synthesized by a facile solvothermal process. Ni11 (HPO3 )8 (OH)6 and Ni11 (HPO3 )8 (OH)6 /rGO cathodes both possess very high initial discharge capacities of 132.4 and 182.0 mA h g −1 at a current density of 200 mA g −1, respectively. In addition, the long-term cycling stability of the Ni11 (HPO3 )8 (OH)6 /rGO cathode is further evaluated, exhibiting a discharge capacity of 49.2 mA h g −1 even over 1500 cycles. More importantly, the redox reaction mechanism of the Ni11 (HPO3 )8 (OH)6 cathode for aluminum-ion batteries revealed that Ni11 (HPO3 )8 (OH)6 is partially substituted with Al 3+ to form Al m Ni n (HPO3 )8 (OH)6 and metallic Ni in the nanorod-like Ni11 (HPO3 )8 (OH)6 cathodes during the discharge process. These findings are of great significance for the further development of novel materials for aluminum-ion batteries.